The Relationship Between Childhood Physical and Sexual Abuse and Adolescent Cannabis Use: A Systematic Review - De la Peña-Arteaga, Víctor; Nogueira, Sarah O.; Lynskey, Michael; Hines, Lindsey A. (Frontiers in Psychiatry, 2021)
Background Among adolescents, cannabis use is a health concern due to associations with drug addiction and mental health disorders across the life course. It has been shown that childhood maltreatment is associated with drug addiction in adulthood. However, a better understanding of the relationship between maltreatment and drug use may improve targeted prevention and interventions. The aim of this systematic review is to describe the association between exposure to childhood maltreatment, specifically physical and sexual abuse, with adolescent cannabis use. Methods A systematic search strategy was applied to Embase, PsycINFO and Ovid MEDLINE(R) databases. Methods followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Abstract and title screening was performed to identify papers which reported an estimate of the association between childhood physical or sexual abuse and adolescent cannabis use. Full text screening of each paper was performed, and data were extracted and study quality assessed. Weighted means meta-analysis was performed on studies reporting odds ratios as effect estimates. Results Of 8780 screened articles, 13 were identified for inclusion. Eight papers received a quality rating score indicating lower risk of bias. Eleven papers reported the relationship between childhood sexual abuse and adolescent cannabis use; effect estimates ranged from AOR 0.53 - AOR 2.18 (weighted mean OR 1.29, 95% CI 1.08 – 1.49). The relationship between childhood physical abuse and adolescent cannabis use was reported in 7 papers; effect estimates ranged from AOR 1.25 - AOR 1.87 (weighted mean OR 1.39, 95% CI 1.12 – 1.66). Differences in the strength of the evidence were observed by the method of exposure ascertainment, and there was some evidence of differences in association by gender, age of cannabis initiation, and the severity of the abuse. Conclusions This systematic review indicates childhood physical or sexual abuse may increase risk of adolescent-onset cannabis use. Few studies considered variation in timing of onset, or by gender. Adolescent cannabis use precedes is strongly associated with increased risk of negative mental health outcomes; further exploration of adolescent cannabis use’s place on the causal pathway between childhood abuse and adult mental health problems is warranted to improve intervention.